2017
DOI: 10.1007/s00109-017-1590-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IX inhibition affects viability of cancer cells adapted to extracellular acidosis

Abstract: Cancer cells overexpress CAIX under transient and chronic extracellular acidosis. Acidosis-induced CAIX overexpression is NF-κB mediated and HIF-1α independent. FC16-670A prevents CAIX overexpression and induces acidified cancer cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…In this study, we provide a prospective combination of treatment that includes an inhibitor of histone deacetylases (HDACs), as their dysregulation is associated with many forms of cancers [29][30][31][32][33][34][35][36] , and an inhibitor of CA IX, as its overexpression in various tumours is correlated with cancer progression and poor survival 17,52 . We have previously reported that melanoma, breast and colorectal cancer cell lines, express high levels of CA IX in normoxia whereas the transiently and chronically exposure to extracellular acidic microenvironment (pH 6.7 ± 0.1) induces CA IX overexpression 53 . Moreover, we demonstrated that SLC-0111, a novel CA IX inhibitor, is able to synergize with cytotoxic drugs such as Dacarbazine, Doxorubicine and 5-Fluorouracil 26 .…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we provide a prospective combination of treatment that includes an inhibitor of histone deacetylases (HDACs), as their dysregulation is associated with many forms of cancers [29][30][31][32][33][34][35][36] , and an inhibitor of CA IX, as its overexpression in various tumours is correlated with cancer progression and poor survival 17,52 . We have previously reported that melanoma, breast and colorectal cancer cell lines, express high levels of CA IX in normoxia whereas the transiently and chronically exposure to extracellular acidic microenvironment (pH 6.7 ± 0.1) induces CA IX overexpression 53 . Moreover, we demonstrated that SLC-0111, a novel CA IX inhibitor, is able to synergize with cytotoxic drugs such as Dacarbazine, Doxorubicine and 5-Fluorouracil 26 .…”
Section: Discussionmentioning
confidence: 98%
“…However, to prevent intracellular H þ accumulation cancer cells upregulates proton exchangers that extrude protons in excess contributing to acidify extracellular tumour microenvironment 9,11,12 . Among these proton exchangers, a primary role is played by CA IX, an enzyme overexpressed in many types of cancers, including prostate cancer, with the potential to represent both a promising tumour biomarker and a specific target for future cancer therapies 13,[30][31][32][33][37][38][39][40][41]44 . Under the pressure of the acidic microenvironment, CA IX expression and activity are upregulated in both tumour cells 30,44 and the exosomes released extracellularly 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed CA IX is the most widely expressed gene in response to hypoxia, playing a pivotal role in tumour pH regulation 13,30,37,41 ; thus conferring to cancer cells a survival advantage in hypoxic and acidic microenvironments 43 . Thus, it is clear that the acidic microenvironment induces the up-regulation of the CA IX expression and activity in both tumour cells 30,44 and tumour released exosomes 30 . However, the possibility that CA IX expression and activity in cancer cell-derived exosomes could represent a new valuable tumour marker has not yet been tested in clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies support SFN as a potent antitumor agent against multiple signaling pathways in diverse cancers and targeting of mitochondrial functions where normal cells are protected [45][46][47][48][49][50]. Expression of carbonic anhydrase IX (CAIX) is highly relevant to rapidly growing and aggressive tumor cells adapting to the acidic microenvironment in rapidly growing tumors in order to maintain a more intracellular physiological pH, and thus inhibitors of CAIX can potently inhibit tumor cell viability [51,52]. Here we show that AZ alone is an effective but more modest growth inhibitory agent.…”
Section: Discussionmentioning
confidence: 99%